2018
DOI: 10.1096/fj.201800554rr
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary epicatechin improves survival and delays skeletal muscle degeneration in aged mice

Abstract: We recently reported that epicatechin, a bioactive compound that occurs naturally in various common foods, promoted general health and survival of obese diabetic mice. It remains to be determined whether epicatechin extends health span and delays the process of aging. In the present study, epicatechin or its analogue epigallocatechin gallate (EGCG) (0.25% w/v in drinking water) was administered to 20-mo-old male C57BL mice fed a standard chow. The goal was to determine the antiaging effect. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…The purpose of this experiment was to identify small-molecule metabolites that are closely related to whole-body vibration. According to the VIP value, which was taken to be higher than 1 as the standard in the OPLS-DA models, the differences in the variables between the YC and AC groups (17) and the AC and AV groups (19) . 2a,b).…”
Section: Screening Results Of Skeletal Muscle Differential Metabolitesmentioning
confidence: 99%
“…The purpose of this experiment was to identify small-molecule metabolites that are closely related to whole-body vibration. According to the VIP value, which was taken to be higher than 1 as the standard in the OPLS-DA models, the differences in the variables between the YC and AC groups (17) and the AC and AV groups (19) . 2a,b).…”
Section: Screening Results Of Skeletal Muscle Differential Metabolitesmentioning
confidence: 99%
“…We have measured the positive impact that the daily provision of oral Epi at low doses (1 mg/kg/day) has on the functional status of such systems leading to greater levels of tolerance to fatigue and tissue damage from challenges such as ischemia (24). Also, recent evidence showed that Epi supplementation slowed down the aging of skeletal muscle in old mice (25). The current report extends such studies to the elderly population in whom loss of muscle mass and other effects of aging decrease exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, epicatechin increased the mRNA expression of MyoD, superoxide dismutase (SOD), and catalase in the biceps femoris muscle and decreased the expression of FoxO3, myostatin, and MuRF1 in the soleus muscle (Hong et al, 2020). Si et al (2019) observed that epicatechin increased the survival rate of aged mice and delayed the degeneration of skeletal muscle. Furthermore, epicatechin gave rise to a positive effect on the skeletal muscle in 26-month-old C57BL/6 mice (Moreno-Ulloa et al, 2015).…”
Section: Epicatechinmentioning
confidence: 93%